PENGARUH KONFLIK KERJA KELUARGA DAN MOTIVASI KERJA TERHADAP STRES KERJA PADA PERAWAT RUMAH SAKIT WULAN WINDY MEDAN - Muhammad Yalzamul Insan (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
Every staff are stressed at work. Organizational interventions were more effective if they improve management including the organization must be paid attention to all nurse. Nurses’ job stress is one of the factors which influence competitiveness among hospitals. Some factors which directly influence nurses’ job stress are the level of work to family conflict, and work motivation. The objective of this research was to find out and to analyze the influence of work to family conflict and motivation on nurses’ job stress at Wulan Windi Hospital. The research used descriptive quantitative and explanatory research method. The population was 54 nurses at Wulan Windi Hospital, and 43 of them were used as the samples, taken by using purposive sampling technique. The number of samples was based on the criteria: the respondents had been married and had children. The data were gathered by conducting interviews, questionnaires, and documentary study. Interval scale was used for measuring scales and the data were analyzed by using multiple linear regression analysis, while residual test and interaction test were used for moderating variable. The result of the research, in the first hypothesis, showed that, partially, work to family conflict had positive but significant influence on nurse’ job stress . The result of the second hypothesis showed that, partially, motivation had negative and significant influence on nurses’ job stress. The result of the third hypothesis showed that work to family conflict and motivation had significant influence on nurses’ job stress.  Keywords: Work to Family Conflict, Work Motivation, Nurses’ Job Stress